2000
DOI: 10.1080/00220970009598498
|View full text |Cite
|
Sign up to set email alerts
|

Getting Students “Partially” Involved in Note-Taking Using Graphic Organizers

Abstract: Encoding benefits (DiVesta & Gray, 1972) of graphic-organizer and outline note-taking using spaced study and review (Robinson, Katayama, Dubois, & DeVaney, 1998) were investigated. In 2 40-min periods separated by 2 days, 117 undergraduates studied a chapter-length text along with a set of complete, partial, or skeletal graphic organizers or outlines. Two days later, the students reviewed their materials for 10 min and then completed factual and application tests. On the factual test, there was no effect for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
3
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 30 publications
4
76
3
6
Order By: Relevance
“…The completed cells likely supported learners by indicating both the topics and subtopics that should be addressed in notes. Similarly, Katayama and Robinson (2000) concluded that in comparison to complete or skeletal matrix notes, partially completed matrix notes are the most effective adjunct aids.…”
Section: Applying the Principles Of Strategy Instructionmentioning
confidence: 99%
“…The completed cells likely supported learners by indicating both the topics and subtopics that should be addressed in notes. Similarly, Katayama and Robinson (2000) concluded that in comparison to complete or skeletal matrix notes, partially completed matrix notes are the most effective adjunct aids.…”
Section: Applying the Principles Of Strategy Instructionmentioning
confidence: 99%
“…This effect is further explored by Katayama and Robinson (2000). They studied the effects of note-taking structure with a 2 (i.e.…”
Section: Structure Of Note-takingmentioning
confidence: 99%
“…Donahoo (2009) also finds that graphic organizers are useful thinking tools that allow students to organize information and allow students to see their thinking. In addition, Katayama et al (2000) conclude that graphic organizer is computationally more efficient than outlines or texts and it engages students in learning, resulting in encoding benefits.…”
Section: Figure 1 Samples Of Graphic Organizermentioning
confidence: 93%
“…Graphic organizer can be defined as a conceptual communicative tool (Katayama et al, 2000) and a series of visual charts and tools used to represent and organize a student's knowledge or ideas. Graphic organizers are often used as part of the writing process to help students map out ideas, plots, character details and settings before beginning to write.…”
Section: Graphic Organizermentioning
confidence: 99%